Social Entrepreneurship as a Driver of Social Innovation in Post-Revolution Tunisia: Evidence from Ten Enterprises in Gabes - ERNEZ, Molka (Journal of Posthumanism, 2025)
This article examines how social entrepreneurs in Gabes (Tunisia) generate and sustain social innovation under institutional fragility. Drawing on an exploratory qualitative study of ten social enterprises supported by the ESS/EV program, we analyze how found-ers identify unmet needs, structure organizational processes, and navigate financing con-straints. The study reveals four features: (i) multidimensional social needs spanning youth unemployment, women’s and disability inclusion, environmental protection, and the valorization of local heritage; (ii) participatory yet vulnerable innovation processes marked by experimentation under scarce resources; (iii) organizational arrangements shaped by territorial context and weak public support; and (iv) reliance on grants with limited access to hybrid finance. Theoretically, we conceptualize the entrepreneur-as-pivot in territorially embedded social innovation and identify financing as a moderator that conditions diffusion and scale. Empirically, we provide rare field-based evidence from the MENA region. Practically, we derive policy implications: hybrid finance mechanisms (e.g., matching grants with revenue-based finance or first-loss guarantees), SSE-specific legal recognition and fiscal incentives, and territorial intermediation to link entrepreneurs with markets and institutions. Together, these measures can convert fragile, do-nor-dependent prototypes into scalable, durable social innovations in Tunisia and com-parable developing economies.